2004
DOI: 10.1038/nature02808
|View full text |Cite
|
Sign up to set email alerts
|

Impact of climate change on marine pelagic phenology and trophic mismatch

Abstract: Phenology, the study of annually recurring life cycle events such as the timing of migrations and flowering, can provide particularly sensitive indicators of climate change. Changes in phenology may be important to ecosystem function because the level of response to climate change may vary across functional groups and multiple trophic levels. The decoupling of phenological relationships will have important ramifications for trophic interactions, altering food-web structures and leading to eventual ecosystem-le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

52
1,345
5
9

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,813 publications
(1,411 citation statements)
references
References 24 publications
52
1,345
5
9
Order By: Relevance
“…A large number of studies have reported that the timing and magnitude of seasonal plankton blooms are shifting in response to climate change (Adrian et al 2006;Edwards and Richardson 2004;Meis et al 2009;Shimoda et al 2011). Plankton blooms are important features in seasonal aquatic environments where they drive many ecosystem and community processes and are a major source of energy input for higher trophic levels (Hjermann et al 2007;Smayda 1997;Winder and Cloern 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies have reported that the timing and magnitude of seasonal plankton blooms are shifting in response to climate change (Adrian et al 2006;Edwards and Richardson 2004;Meis et al 2009;Shimoda et al 2011). Plankton blooms are important features in seasonal aquatic environments where they drive many ecosystem and community processes and are a major source of energy input for higher trophic levels (Hjermann et al 2007;Smayda 1997;Winder and Cloern 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Since recently, the impact of climate variability on aquatic ecosystems has been in the focus of aquatic research (e.g., Wiltshire and Manly 2004;Edwards and Richardson 2004;Winder and Schindler 2004). The relation between climate and the ecosystem is understood as an abiotic control, possibly subject to anthropogenic influences, that causes a biotic response, (e.g., Engel et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Although this is the case, the observed relationship between temperature and productivity underscores the importance of continuing to monitor the species in Alaska where warming is expected to be most intense (IPCC 2013). In addition to temperature and precipitation effects, climate change and ocean acidification could change the base of the marine food web (Edwards & Richardson, 2004; Kroeker, Kordas, Crim, & Singh, 2010; Lam, Cheung, & Sumaila, 2016), the timing of salmon runs (Quinn, Hodgson, Flynn, Hilborn, & Rogers, 2007), and distribution of nesting substrate (Miller, Wilson, Sherriff, & Walton, 2017). These factors may influence bald eagle nesting populations in the future.…”
Section: Discussionmentioning
confidence: 99%